Presence of Shiga-toxin producing Escherichia coli and Escherichia coli O157: H7 in local beef and Indian buffalo meat - Kwan, Sin Yen (2018)
Shiga-like toxin producing Escherichia coli bacteria are well known to be the pathogenic bacteria that cause traveller diarrhea. E. coli O157: H7 from the group of Shiga-like toxin producing E. coli cause even severe infection which can lead to fatal in human. In this study, local beef and India buffalo were selected to determine the presence of Shiga-like toxin producing E. coli and E. coli O157:H7 using Most Probable Number-Polymerase Chain Reaction (MPN-PCR) method. Among one hundred and eight samples, eight samples from local beef and India buffalo were detected a positive on E. coli O157: H7 while thirteen samples were detected positive for Shiga-like toxin producing E. coli gene. Out of 108 samples (n=108), 11 isolates of E. coli O157: H7 were successfully isolated in order to carry out the antibiotic susceptibility test. Shiga-like toxin producing E. coli isolates were found susceptible to ceftazidime (100%), moxifloxacin (83.33%), sulphamethoxazole (66.67%), ampicillin (50%), amoxycillin (50%), ciprofloxacin (50%), erythromycin (33.33%) and penicillin G (33.33%). E. coli O157: H7 isolates were susceptible toward erythromycin (100%), ceftazime (100%), ciprofloxacin (100%) and moxifloxacin (100%), sulphamethoxazole (60%), ampicillin (20%), amoxycillin (20%), and penicillin G (0%). In conclusion, both Shiga-like toxin producing E. coli and E. coli O157: H7 were detected from both local beef an India buffalo. In this research, effect of holding time and washing practice on growth pattern of E. coli O157:H7 on beef was studied. Beef samples that were washed and remain un-washed were placed in room temperature. Washed samples present a lower bacteria count. However, the longer the beef was placed under room temperature, the more the bacteria count detected on beef sample. It is recommended to keep raw meat immediately in fridge or freezer after purchase or thawing raw meat overnight in fridge (4 °C).